Efecto de la aplicación visme en el diseño de infografías con estudiantes de cuarto de secundaria en la I.E. Teniente Manuel Clavero Muga, Iquitos 2023 - Lozan Sanchez, Alexia Xiomara (2024)
The main objective of this main objective of this research was to determine the effect of the Visme application on the the Visme application in the design of infographics with 4th grade students at I.E. TNT. high school students at I.E. TNT. Manuel Clavero Muga - Iquitos, in the year 2023. The dimensions taken as dimensions were the format and the design of infographics. dimensions were taken as the format and organization of the infographics. The The study was developed in an experimental way, where the quasi-experimental method was applied, since there were two groups, one of them experimental method was applied, with two groups, one experimental and one control group, of the 172 students in the population, a group of 69 students were selected for the sample of the 172 students in the population, a group of 69 students were selected for the sample, from which the two groups of 34 and 35 sample units were formed. and 35 sample units were formed, using a questionnaire and a collection sheet to collect the necessary information. questionnaire and a data collection sheet, where both both instruments were subjected to the content validity test and the reliability test content validity test and reliability test, giving in both cases positive results to be applied and as main results it was possible to determine that with a p-value = 0.5. p-value = 0.000 < 0.05; it can be affirmed that the Visme application improves the design of infographics in 4th grade students infographics in 4th year high school students at I.E. TNT. Manuel Clavero Muga - Iquitos, in the year 2023, concluding that the use of the Visme application improves the design of infographics in students.